PENGARUH KUALITAS LAYANAN INTERNET BANKING SECARA KESELURUHAN TERHADAP KEPUASAN PELANGGAN (Studi Kasus pada Bank BNI Pekalongan) - Siti Nurhayati; Wenti Ayu Sunarjo (LPPM Universitas Pekalongan, 2013)
Abstract The aims of this research is to analize the dimensions of internet banking, there have 3 dimensions : (1) online customer service quality, (2) online information system quality, and (3) banking service product quality, and their influence to customer’s satisfaction. The analyze done by intervening regression model with SPSS, and than examine both partial and simultaneous hypothesis. The sample amount 152 customers of BNI Pekalongan that using the internet banking service. The procedures of analysis are : a. testing the instrument with validity and reliability, b. testing the classic assumption with normality, multicolinearity,and heteroscedasticity, c. intervening regression analysis with 2 models (substructure) regressions, d. testing the partial and simultan hypothesis The result of substructure 1 regression, show that on partial test, 3 independent variables above has the positive and significance influence to overall internet banking quality service at the level of significance 95 % ( or at α 5 % ). On the simultaneous test also has the significance influence result. The test hypothesis of substructure 2 regression, showthat overall internet banking quality service has the significance influence. By those result, the management of BNI Pekalongan must optimalized the quality of internet banking service that can increasing the customer’s satisfaction, because it was make the positive effect of corporate image by the word of mouth informations. KEYWORDS : customer service; information system internet banking